Giant cell tumor of the thoracic spine: An unusual cause for spinal cord compression - Ghassen Gader; Fatma Ben Attig; Wiem Mansour; Abdelhafidh Slimane; Malek Bourgou; Mohamed Badri; Ihsèn Zammel (Radiology Case Reports)
Giant cell tumors (GCTs) of bone are uncommon neoplasms, typically located in the metaphysis of long bones, with rare occurrences in the spine, especially in the thoracic region. We report the case of a 34-year-old woman with a history of psoriasis and celiac disease, who presented with progressive inflammatory back pain and paraparesis. Imaging revealed an osteolytic mass at the T11 vertebra, causing dorsal spinal cord compression. Emergency surgery was performed, with histopathology confirming GCT. Despite initial recovery of motor function, surgical stabilization was later necessary to prevent spinal instability. The patient was started on adjuvant Denosumab therapy and remained asymptomatic on follow-up. This case highlights the rarity of GCT in the thoracic spine and associated diagnostic and therapeutic challenges. Though benign, GCTs can cause severe spinal cord compression, necessitating prompt surgical intervention to preserve neurological function. Denosumab therapy shows promise in controlling tumor progression and enhancing surgical outcomes. Multidisciplinary management and regular follow-up are essential to prevent recurrence and improve prognosis.